How the competitive exclusion principle can be validated using optical density measurements collected on artificially reconstituted soil ecosystems - Miled EL Hajji (Open Journal of Environmental Biology - Peertechz Publications, 2019)
A mathematical model, validated on experimental data aiming at describing and predicting soil bacteria growth on an essential limited substrate in batch pure cultures is proposed as an extension of the Monod's one in revisiting the way where the optical density is modelled. This model takes into account viable cell growth, substrate consumption, cell mortality, non-viable cell accumulation in the culture medium and partial dead cell recycling into substrate. The least squares method is used to identify model parameters. The model is extended and validated for mixed cultures proving, for artificially reconstituted soil ecosystems, that there is only competition for the substrate. Mathematics Subject Classification: 34D23, 35N25, 37B25, 49K40, 00A71.